Petrology of the Swat Amphibolites and the Development of a “Lesser Himalayan” Basin - Humayun, Munir (Journal of Himalayan Earth Sciences, 1986)
A geochemical study of amphibolites from the lower Swat valley, Lesser Himalaya, identifies a suite of continental flood basalts erupted over a gneissic basement of probable Late Cambrian age. Fractionation of clinopyroxene and plagioclase controlled chemical variation in the protolith. Metamorphism, retrogression and granitic intrusion strongly affected the alkali and mobile trace element contents. The magmatism was probably associated with the early rifting stage of the development of Paleotethys. Subsidence of the rifted margin followed the extrusion of the basalts, and arkosic continental sediments gave way to marine carbonates and clastics. The carbonates belong to a reefoid association of Middle Paleozoic age. The basin extended over much of present day northwestern Pakistan with probable analogues along the length of the Lesser Himalayas.